Analisis Faktor Risiko yang Mempengaruhi Kolesterol: Cross-sectional study - Nurseto Jati Wijoyo; Nurulia Hidayah; Nur Rokhman Rosyid; Rita Dian Pratiwi (Universitas Hang Tuah Pekanbaru, 2026)
The increasing incidence of hypercholesterolemia among employees may affect cardiovascular health and workplace productivity. In Indonesia, the Basic Health Research (Riskesdas) 2018 reported that 35,9% of adults have elevated cholesterol levels. This study aimed to analyze the risk factors associated with total cholesterol levels among employees and to determine the most dominant influencing factor. This study employed a quantitative approach with a cross-sectional design. Data were obtained from company medical check-up records and physical activity questionnaires using the International Physical Activity Questionnaire. The independent variables included age, blood pressure, smoking habits, obesity, exercise routine, and gender, while the dependent variable was total cholesterol level. Data were analyzed using chi-square test and binary logistic regression. The results showed that high blood pressure (PR = 16.5; p < 0.001), obesity (PR = 3.646; p = 0.035), and irregular exercise (PR = 5.633; p = 0.013) were significantly associated with elevated total cholesterol levels. Multivariate analysis indicated that high blood pressure was the most dominant risk factor influencing total cholesterol levels (PR 15.569; p < 0.001). Maintaining normal blood pressure, regular physical activity and weight management are essential strategies to workplace health improvement.